Electro‐Blown Spun Silk/Graphene Nanoionotronic Skin for Multifunctional Fire Protection and Alarm. Issue 38 (2nd August 2021) - Cao, Leitao; Liu, Qiang; Ren, Jing; Chen, Wenshuai; Pei, Ying; Kaplan, David L.; Ling, Shengjie
Abstract: Artificial protective skins are widely used in artificial intelligence robots, such as humanoid robots, mobile manipulation robots, and automatic probe robots, but their safety in use, especially flame retardancy, is rarely considered. As many artificial skins are designed for use in flammable or even explosive environments, flammability is a significant concern. Herein, a flame‐retardant silk/graphene nanoionotronic (SGNI) skin is developed by using a rationally designed high‐throughput electro‐blown spinning technique, with a more efficient production efficiency than electrospinning. These flame retardant SGNI skins combine the advantages of nanofibrous and ionotronic materials, and they are sustainable, conductive, highly porous, mechanically robust, highly stretchable, self‐adhesive, and humidity‐ and temperature‐sensitive. These merits support the assembly of SGNI skins into a fire alarm system, with real‐time alarm (response in 2 s) to mobile phones, clouds, and a central control system. The concept that combines a flame retardant and fire alarm material into an intelligent skin may provide potential solutions toward the design of protective skins for robotics and human–machine interactions. Abstract : A flame‐retardant silk/graphene nanoionotronic (SGNI) skin with sensitive fire alarm property is fabricated using electro‐blown spinning. The SGNI skin adheres to the target surface and serves as an alarm. Once exposed to fire, the SGNI skin senses the fire source and quickly sends an alarm to the control center and a cell phone.